2022
DOI: 10.1128/jvi.00389-22
|View full text |Cite
|
Sign up to set email alerts
|

Single Immunization with Recombinant ACAM2000 Vaccinia Viruses Expressing the Spike and the Nucleocapsid Proteins Protects Hamsters against SARS-CoV-2-Caused Clinical Disease

Abstract: Continuous emergence of SARS-CoV-2 variants which cause breakthrough infection from the immunity induced by current spike protein-based COVID-19 vaccines highlights the need for new generations of vaccines that will induce long-lasting immunity against a wide range of the variants. To this end, we investigated the protective efficacy of the recombinant COVID-19 vaccine candidates based on a novel VACV ACAM2000 platform, in which an immunoregulatory gene, E3L, was deleted and both the SARS-CoV-2 spike (S) and n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Another study reported that T-cell responses to S and N antigens after dual-antigen hAd5 S + N prime vaccination alone were equivalent to those from previously SARS-CoV-2-infected patients, and in silico prediction models of T-cell epitope HLA binding suggested that T-cell responses to the hAd5 S + N vaccine will retain their efficacy against the B.1.351 variant. Moreover, plasma from previously SARS-CoV-2-infected patients showed a higher binding affinity to cells expressing the dual antigen S-Fusion + N-ETSD construct than to the hAd5 S-Fusion alone, further suggesting that the immunogenicity of the S + N double-antigen vaccine is better than that of the S single-antigen vaccine [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study reported that T-cell responses to S and N antigens after dual-antigen hAd5 S + N prime vaccination alone were equivalent to those from previously SARS-CoV-2-infected patients, and in silico prediction models of T-cell epitope HLA binding suggested that T-cell responses to the hAd5 S + N vaccine will retain their efficacy against the B.1.351 variant. Moreover, plasma from previously SARS-CoV-2-infected patients showed a higher binding affinity to cells expressing the dual antigen S-Fusion + N-ETSD construct than to the hAd5 S-Fusion alone, further suggesting that the immunogenicity of the S + N double-antigen vaccine is better than that of the S single-antigen vaccine [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The S + N group had low viral RNA copies in the lung, reduced weight loss, and a quick recovery time post-SARS-CoV-2 challenge compared to the group immunized with S/N alone, which was consistent with the results of this study. However, none of the groups detected the neutralizing antibody titers, which might be explained by differences in vaccine variety and experimental animals [ 26 ]. One SARS-CoV-2 adenovirus vector vaccine study reported that the S vaccine only provided acute brain protection when co-immunized with an N vaccine [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus N protein is the most abundant and highly antigenic structural protein ( 57 ). Several COVID-19 vaccine candidates based on the application of both spike and N as antigens have been shown to be protective against SARS-CoV-2 challenge in animal models such as hamsters and nonhuman primates (NHPs) ( 58 – 60 ). Here, we found that N is a dsRNA binding protein capable of inhibiting PKR- and OAS/RNase L-mediated antiviral activities.…”
Section: Discussionmentioning
confidence: 99%
“…While rACAM2000 vaccination leads to higher neutralizing antibody titers following SARS-CoV-2 challenge, rACAM2000N vaccination does not. This finding suggests that cell-mediated immune responses are likely responsible for the protection afforded by rACAM2000N ( Deschambault et al, 2022 ).…”
Section: Nucleocapsid-based Sars-cov-2 Vaccinesmentioning
confidence: 95%